RELASI AKTIVITAS DAN BENTUK DAPUR RUMAH TINGGAL DI KAWASAN PINGGIRAN KOTA YOGYAKARTA - Freddy Marihot Rotua Nainggolan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2016)
Title: The Relation Between Activities and the Shape of Home Kitchen in The Suburbs of Yogyakarta Globalization has made all information and technologies quickly reach other regions. Suburbs suspected of having such impacts caused by the influence of change. The kitchen is a room with a unique because of the space directly related to the fire and growing rapidly in technology equipment inside, that allegedly subjected to the influence of globalization. This research is qualitative rationalistic to see the activities and functions through the shape of home kitchen in the suburbs of Yogyakarta. Six samples with the functional categories of residential houses, vernacular style, has a kitchen that is changing and the owners who lived with two or more generations and are natives selected as research objects. The finding is the unification of kitchen to the main house through an intermediary space and adaptation of kitchen work triangle in transformation of form.